Insights into phase engineering and morphological tailoring of WS2 nanostructures via temperature controlled hydrothermal synthesis - Somveer; Dharamvir Singh Ahlawat; Davender Singh; Bijender Singh; Jitendra Gangwar (Nano Express)
Present work emphasizes on designing multiphase (1T and 2H) WS _2 materials with fascinating controlled morphology in 3D (nanoflowers) and 1D (nanorods and nanowires) systems via a cost-effective solvo- and hydro-thermal method as well as comparing the effect of temperatures (200 and 210 °C) on distinctive properties. 1T- and 2H-WS _2 nanostructures exhibit the dependence of crystallite size, morphology, stoichiometry and constituents homogeneity on synthesis temperatures. Investigations using different spectroscopic and microscopic techniqus reveal that the high temperature is implemental to produce effective nanostructured WS _2 materials. The nanostructures 1T-WS _2 and 2H-WS _2 poses metallic and semiconducting characteristics, respectively. On the basis of initial experimental analyses, a plausible formation- and growth-mechanism is elucidated for both 1T- and 2H-WS _2 nanostructures. Consequently, the facile preparation offers a great promise for developing heterostructures modified with multiphase WS _2 and indicates a potential path way for both fundamental and application based researchers to continue further advancement in sensing and fuel cell technology.